Iot-Based Smart Wardrobe Dehumidifier: A Tech Solution for Moisture Control and Fabric Protection - Vaisakh A, Vaisakh A; .K.Selvavinayaki, .K.Selvavinayaki; Uvais, Mohammed; Khan, Mumtaz; Priyamvatha, Priyamvatha; Silja, Silja; Pavithra, Pavithra (Journal of Neonatal Surgery, 2025)
Excess humidity in wardrobes can lead to mold growth, musty odors, and fabric deterioration. A smart wardrobe dehumidifier offers an innovative solution by maintaining optimal humidity levels through automated sensing and control. Utilizing IoT technology, it enables real-time monitoring, remote operation, and energy-efficient moisture removal, ensuring the longevity of stored clothing and accessories. This smart system enhances wardrobe hygiene, prevents allergen buildup, and protects delicate fabrics such as leather and wool. By integrating advanced dehumidification techniques with intelligent automation, this solution provides a convenient and effective approach to wardrobe maintenance